A Study To Explore The Factors Of Training In Enhancing Employee Performance In Automobile Industry - Saxena, Mayank; Dhar, Prafulla Chandra (Journal of Neonatal Surgery, 2025)
Training plays a crucial role in improving employee performance, particularly in the automobile industry, where technological advancements and quality standards are constantly evolving. This study aims to explore the key factors influencing training effectiveness and their impact on employee performance. The research employs a mixed-method approach, combining surveys and interviews with employees and training managers from leading automobile firms. The findings suggest that structured training programs, management support, technological integration, and continuous learning significantly enhance employee productivity, efficiency, and job satisfaction